ANALISIS SEKTOR EKONOMI BASIS KECAMATAN KEMBAYAN TERHADAP KABUPATEN SANGGAU - B01107086, Rahmad Sanjani (Jurnal Pembangunan dan Pemerataan, 2013)
This Skripsi entitle " Analysis Economic Sector Bases District of Kembayan To Sub-Province Sanggau", this skripsi of background overshadow by activity of economics of District of Kembayan during range of time 5 year ( 2006-2010). This research aim to to know bases economic sector or pre-eminent sector of District of Kembayan and also compare and analyse economic growth rate of District of Kembayan to economic growth rate of Sub-Province Sanggau. used by Method Research at this research is descriptive analysis that is by explaining and depicting an situation / occurence as it is and as according to existing condition. With source of sekunder data which in can through institution / related / relevant on duty and also evaluate respective bibliography, while in analysing data use analyzer in the form of Location Quotient analysis ( LQ), analyse Shift-Share ( SS) And Tipologi Klassen analysis utilize to answer existing problems. From result of research third the analysis can know that is, pursuant to Location Quotient analysis ( LQ) known that in District of Kembayan there is four sector representing bases economic sector or pre-eminent sector which is its value of big from one that is agricultural sector equal to 1,59, building sector equal to 1,15, transportation sector and communications equal to 1,44, and also service sector equal to 1,26, while other sector with LQ value less than one. From result of Shift-Share analysis known that during range of time five PDRB year District of natural Kembayan of increase of performance economics of area equal to Rp 9,54 billion, with four sector which is kompetitif that is agricultural sector, mining sector and dig, electrics sector and drinking water, and also commercial sector, restaurant and hotel. Later;Then for industrial hotchpotch indicate that economics of District of Kembayan affect negativity with the meaning there no influence from industry to output yielded by economics of District of kembayan. While pursuant to result of Tipologi Klassen analysis known that agricultural sector represent sector staying in prima classification, at potential classification there is three sector that is building sector, transportation sector and communications, and also service sector. Next at classification expand also there is three sector that is mining sector, electrics sector and drinking water, and also commercial sector, restaurant and hotel, while at situated behind classification there is two sector that is processing industrial sector, and also financial sector, company service and rental. Key word : Location Quotient (LQ), Shift-Share (SS), Klassen Thypology